The Paradox of Clean Eating: Neuroactive Dysbiosis and Pesticide Residues in Fruit- and Vegetable-Based Diets - Ramona Alina Tomuța; Andrada Florina Moldovan; Loredana Matiș; Lavinia Maris; Timea Claudia Ghitea; Florin Banica (Toxics)
(1) Background: Exposure to pesticide residues through food remains a critical issue in public health, especially given their potential cumulative neurotoxic effects. (2) Methods: This study investigated the presence of pesticide residues in commonly consumed vegetables, fruits, and cereals based on official laboratory reports and evaluated the intestinal microbiome profiles of individuals whose diets consisted of over 50% plant-based foods. (3) Results: Analytical results from accredited laboratories in Romania demonstrated that all tested food samples were compliant with European regulations (Regulation (EC) 396/2005), with either undetectable or below-quantification-limit pesticide residues. However, organophosphates such as chlorpyrifos and diazinon were frequently tested, indicating persistent regulatory concern due to their known neurotoxic potential. A parallel analysis of stool samples revealed significant imbalances in neuroactive gut bacteria, including consistently low levels of Bifidobacterium and Lactobacillus species, and elevated levels of Oscillibacter and Alistipes, which are implicated in modulating GABA and serotonin pathways. Markers of proinflammatory activity, such as LPS-positive bacteria and histamine producers, were also elevated. (4) Conclusions: These findings suggest that even in diets rich in plant-based foods, microbial dysbiosis with neuroactive relevance can occur, potentially linked to environmental or dietary factors. The study underscores the need for a comprehensive evaluation of food safety and microbiome function as interconnected determinants of neurological health.